Anal heterosex among young people and implications for health promotion: a qualitative study in the UK. Issue 8 (18th July 2014) - Marston, C; Lewis, R
Abstract : Objective: To explore expectations, experiences and circumstances of anal sex among young people. Design: Qualitative, longitudinal study using individual and group interviews. Participants: 130 men and women aged 16–18 from diverse social backgrounds. Setting: 3 contrasting sites in England (London, a northern industrial city, rural southwest). Results: Anal heterosex often appeared to be painful, risky and coercive, particularly for women. Interviewees frequently cited pornography as the 'explanation' for anal sex, yet their accounts revealed a complex context with availability of pornography being only one element. Other key elements included competition between men; the claim that 'people must like it if they do it' (made alongside the seemingly contradictory expectation that it will be painful for women); and, crucially, normalisation of coercion and 'accidental' penetration. It seemed that men were expected to persuade or coerce reluctant partners. Conclusions: Young people's narratives normalised coercive, painful and unsafe anal heterosex. This study suggests an urgent need for harm reduction efforts targeting anal sex to help encourage discussion about mutuality and consent, reduce risky and painful techniques and challenge views that normalise coercion.